A PROSPECTIVE STUDY OF CLINICAL PROFILE OF STROKE IN A TERTIARY CARE HOSPITAL - Kuriakose, Chachu; M, Naseem Shifafiya; Tharakan, Nelta S; K, Sattanathan; R, Sambath Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The objective of the work was to study the clinical profile of stroke in a tertiary care hospital. Methods: A prospective observational study on stroke was carried out for a period of 6-month (May 2015 to October 2015). A total of 241 inpatients from Shri Preethi Hospital were incorporated in the study. The data were collected and evaluated by reviewing case files and patient interview. Result and Conclusion: Out of 241 patients, an incidence of ischemic stroke was found to be higher. The occurrence of stroke steeply rises with age with male predominance. The burden of stroke tends to be more in rural, illiterate, and low socioeconomic status population. The study reveals risk factors such as sedentary lifestyle, previous and family history of stroke, underlying disease like hypertension, diabetes. The circadian pattern in onset showed a significant peak in morning (6 am-12 pm) for Ischemic and afternoon (12 pm-6 pm) for hemorrhagic stroke. Topographic distribution of cerebral infract and hemorrhage was found to be in parietal lobe and periventricular white matter, respectively. Mostly prescribed medication for ischemic and hemorrhagic patients was antihypertensive and mannitol, respectively. The contraindication for thrombolytic therapy was found to be low economic status and average delay in time of presentation to hospital. The study highlights the need for aggressive management of traditional risk factors, need for extensive work up in patient to find etiologies and need for more active interventions in community for the prevention of stroke. Keywords: Ischemic, Hemorrhagic, Circadian pattern, Antihypertensive.